A Critique Of Islamic Religious Education Learning At Senior High Schools (Case study at MAN 1 Ciamis and SMA Plus Darussalam Ciamis. Cijeungjing District, Ciamis Regency) - Abdusalam, Agus; Kusuma, Deni Tata; Ruswandi, Uus; Arifin, Bambang Samsul (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This study aims to explore the effectiveness of Islamic Religious Education (PAI) learning in MAN 1 Ciamis and SMA Plus Darussalam Ciamis, two institutions integrated with pesantren education under the auspices of the Darussalam Ciamis Islamic Boarding School. The research method used a qualitative approach with structured interview techniques to the principal, curriculum vice-secretary, PAI teachers, and related school parties. Direct observation was conducted with students to get an overview of their perceptions of PAI learning. The results showed that the integration of formal education and pesantren in MAN 1 Ciamis and SMA Plus Darussalam Ciamis created a holistic and value-oriented learning environment. Students respond positively to this approach, although faced with the challenge of adjusting to two different educational patterns. PAI teaching in the classroom is well received by students, while pesantren activities provide an additional dimension in the understanding of Islamic values. The challenges identified involve students' adjustment difficulties, lack of resources, and managerial constraints. Therefore, solutions were proposed through improved curriculum management, adequate resource allocation, and training for teachers. In conclusion, the integration between formal education and Islamic boarding schools in PAI learning has great potential to shape a generation that has a deep understanding of Islam, a strong character, and a balance between academic knowledge and religious practice. With the full support of schools, boarding schools, and the government, efforts can continue to be made to improve the effectiveness of PAI learning in an educational environment integrated with Islamic boarding schools.